Hypoxia-Induced Pulmonary Blood Redistribution in Subjects With a History of High-Altitude Pulmonary Edema - Hanaoka, Masayuki; Tanaka, Masao; Ge, Ri-Li; Droma, Yunden; Ito, Atsuko; Miyahara, Takashige; Koizumi, Tomonobu; Fujimoto, Keisaku; Fujii, Tadashige; Kobayashi, Toshio; Kubo, Keishi (Circulation (New York, N.Y.), 2000)
Background —Pulmonary hypertension has been suggested to play an important role in development of high-altitude pulmonary edema (HAPE), and individual susceptibility has been suggested to be associated with enhanced pulmonary vascular response to hypoxia. We hypothesized that much greater pulmonary vasoconstriction would be induced by acute alveolar hypoxia in HAPE-susceptible (HAPE-s) subjects and that changes in pulmonary blood flow distribution could be demonstrated by radionuclide study. Methods and Results —We performed ventilation-perfusion scintigraphy in 8 HAPE-s subjects and 5 control subjects while each was in the supine position and acquired functional images of pulmonary blood flow and ventilation under separate normoxic and hypoxic (arterial oxygen saturation, 70%) conditions. We also measured acceleration time/right ventricular ejection time (AcT/RVET) with Doppler echocardiography under each condition in both groups. Moreover, we assayed human leukocyte antigen (HLA) alleles serologically in the HAPE-s group. Pulmonary blood flow was significantly shifted from the basal lung region to the apical lung region under hypoxia in HAPE-s subjects, although no significant change in regional ventilation was observed. With Doppler echocardiography, HAPE-s subjects showed increased pulmonary arterial pressure during hypoxia compared with control subjects. The magnitude of cephalad redistribution of lung blood flow was significantly higher in the HLA-DR6–positive than in HLA-DR6–negative HAPE-s subjects. Conclusions —These findings suggest that acute hypoxia induces much greater cephalad redistribution of pulmonary blood flow that results from exaggerated vasoconstriction in the basal lung in HAPE-s subjects. Furthermore, pulmonary vascular hyperreactivity to hypoxia may be associated with HLA-DR6.